EXPLORING IMPACTS OF TEACHER PROFESSIONAL EDUCATION (PPG) ON TEACHER PRACTICE: A CASE OF TWO EASTERN INDONESIAN RURAL SCHOOL TEACHERS - Mukrim, Mukrim; Einsenring, Moh. Abraham Akbar; Hastini, Hastini; Hasyim, Zarkiani (Jurnal As-Salam, 2023)
Several studies have shown the benefits of joining the teacher education profession (PPG) for English teachers. However, little research still exists on its positive impact on teachers in disadvantaged or rural areas. This research examines the benefits received by English teachers in rural areas in eastern Indonesia. This qualitative case study research examines teachers from Central Sulawesi and East Nusa Tenggara as PPG Tadulako University 2022 alums. Data was collected using in-depth interviews and supported by documentation data and observations during the PPG period. The thematic analysis results show that teacher participation in PPG impacts increasing pedagogical knowledge and skills, increasing teacher awareness, and changing teaching practices, ultimately impacting student motivation in learning. This research contributes to the discourse on teacher professionalism development to improve the quality of teachers and education in Indonesia, especially teachers in rural areas.